The Effect of Environmental, Social, & Governance (ESG) Disclosure and Tax Avoidance on Cost of Capital with Firm Size as a Moderating Variable - Faisal Pradana, Ades (Green Publisher Indonesia, 2024)
The purpose of this study is to examine the effect of Environmental, Social, and Governance (ESG) disclosure and tax avoidance on the cost of capital, with firm size serving as a moderating variable. The population of this study consists of all companies listed on the Indonesia Stock Exchange (IDX) that have been included in the SRI-KEHATI index at least once, focusing on the 2018-2021 period. The sample was obtained through a purposive sampling method, and a total of 121 companies were included in the analysis. The results of the study show that ESG disclosure has a negative effect on the cost of capital, indicating that companies with better ESG practices can reduce their cost of capital. Conversely, tax avoidance was found to have a positive effect on the cost of capital, suggesting that companies engaging in tax avoidance face higher costs of capital due to the perceived risks or uncertainties related to their tax practices. Additionally, firm size was found to strengthen the relationship between ESG disclosure and tax avoidance on the cost of capital, indicating that larger firms experience more pronounced effects of ESG practices and tax strategies on their capital costs. This research contributes to the understanding of how ESG disclosure and tax strategies influence financing costs, especially for larger firms in the Indonesian market.